Wavelet and Lipschitz exponent based damage identification method for beams using mode shapes. (December 2022) - Ma, Qiaoyu; Solís, Mario; Rodríguez-Mariscal, José Daniel; Galvín, Pedro
Abstract: This paper presents a damage identification method for beam-type structures based on the wavelet analysis. The damage location is predicted by a Damage Locating Index (DLI) based on a combined identification of local maxima from the scalograms of mode shapes. A new Damage Severity Index (DSI) based on the Lipschitz exponent is formulated such that it is not dependent on the damage locations, boundary conditions, and mode order, as long as a high enough number of measuring points is considered. This study focuses on its application using relatively few measurement points and on the consistency of the DSI. Results from a beam with double-notch damage are analyzed. The results show that the method is applicable with a sparse measurement grid and the DSI Reference values from a static analysis can be referred for damage evaluation using modal displacements. The practical limits of the method are also discussed. Highlights: The proposed method is applicable to mode shapes with sparse measurement points. The proposed DLI is robust to the oscillation of wavelet function. The proposed DSI is valid for modal and static analysis. The DSI is independent on damage locations, boundary conditions, and mode orders. Accurate prediction results are obtained for multi-damage scenarios.